Fundamental Issues in Self-Excited Chatter in Grinding - Entwistle, Rodney; Stone, Brian (Editorial Institution of the Wroclaw Board of Scientific Technical Societies Federation NOT, 2013)
The modelling of chatter in grinding is more complex than for metal cutting. This is because the number of parameters that influence the onset of chatter in grinding is daunting. Also, unlike metal cutting, the growth of chatter in grinding may take a significant time and so growth rates are also important. Initially the modelling of grinding chatter was simply an extension of that already developed for metal cutting. However this was soon found to be inadequate and the models were increased in complexity to include improved grinding force models, the contact stiffness of the wheel and regeneration of surface waves on both the work and wheel. Some solutions to chatter in grinding were also proposed. Most notably these included the use of varying speed and flexible grinding wheels. This position paper re-visits the almost universal assumption that grinding chatter is always regenerative. It is shown that a grinding force model for oscillating conditions, that has been experimentally confirmed, indicates that both torsional vibration and non-regeneration need to be considered. The consequences for current methods of chatter elimination are discussed.